Estratégia de controle aplicada a um inversor fonte de corrente de único estágio com tensão de saída senoidal amplificada - Garcia, Lucas Sampaio (2010)
Renewable energy sources has been attracting great interest due to well known environment issues and, hence, the development of power electronics converters to deal with the transformation of these sources into conventional energy forms has been the main challenge faced by many researches working in this area of expertise. Within this subject, this paper focuses the establishment of a new control strategy applied to a step-down/step-up single-stage inverter with imposed waveforms of CSI inductor current and output voltage. The proposed control strategy provides high voltage gain without using high frequency transformer, which contributes to weigh and size reduction of the proposed DC-AC converter structure. Theoretical and simulation analysis are presented and corroborated by experimental results of a 180W laboratory prototype.